(untitled) (Journal of Business and Technology (Dhaka), 2013)
This study is conducted to identify the factors that motivate the customers to select commercial banks for their valuable transactions. Necessary data are collected from 206 respondents. It is found that easy account opening is the most important variable as it has the highest mean value 4.25. From varimax rotation matrix it is observed that responsiveness is the most important factor to customers which includes friendliness, personality, counseling and foreign exchange service. Special services such as loan and deposit schemes, electronic fund transfer service, cash management service, merchant banking, supporting the customer in bad time have also been found as important. Convenience, assurance, reliability and safety factors are also of considerable importance to customers to choose a bank. DOI: http://dx.doi.org/10.3329/jbt.v7i2.16452 Journal of Business and Technology Vol.7(2) 2012: 19-35